Photographing nature : a photo workshop from Brooks Institute's top nature photography instructor - Clevenger, Ralph A. (New Riders, 2010)
25 years of nature photography instruction in one gorgeous, full-color, hands-on course Anyone can photograph nature--just step outside and you're on location. But becoming a good nature photographer takes expert training. In Photographing Nature, Ralph Clevenger, whose images have appeared in such publications as Nature's Best and National Geographic, shares the techniques he's been personally using and teaching to aspiring photographers for the last 25 years in his popular nature photography course at the elite Brooks Institute. In this stunning, four-color course-in-a-book, each chapter opens with a spectacular photo spread from the natural world that Clevenger uses to illustrate themes and techniques essential to mastering nature photography. Just as he does in his classroom at Brooks, Clevenger explains how each photo was captured, the tools and techniques used, and typical problems related to capturing such a photo, along with solutions. Chapters also include sample Q&A sessions as well as assignments you can try yourself. By the time you've worked through all of the techniques in this beautiful, yet informative book, you'll not only photograph the world differently, you'll see it differently as well. With a foreword by George Lepp, one of North America's best-known contemporary outdoor and nature photographers.